Types of Literature in the Book of Mormon: Epistles, Psalms, Lamentations - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
The Book of Mormon contains nine epistles—two pastoral, one prophetic, and six war epistles. The "Psalm of Nephi" is the only psalm in the Book of Mormon, called such because it is a song of praise, betraying deep religious feeling. A good example of lamentation literature occurs in Mormon 6.